Thermodynamic analysis of hydrogen-rich syngas production with a mixture of aqueous urea and biodiesel. (5th April 2018) - Wu, Horng-Wen; Lin, Ke-Wei
Abstract: An auxiliary power unit based on a solid oxidation fuel cell for heavy-duty vehicles has been receiving attention for high efficiency, low emissions, and more comfort and safety in vehicles. This study explores hydrogen-rich syngas production via reforming of a mixture of aqueous urea and biodiesel by thermodynamics analysis. The aqueous urea is available from Adblue used in a selective catalyst reduction providing efficient control of nitrogen oxides from heavy-duty vehicles to minimize particulate mass and optimize fuel consumption. The results show that at a reaction temperature of 700 °C, urea/biodiesel ratio = 3, and oxygen/biodiesel ratio = 9, the highest reforming efficiency is 83.78%, H2 production 30.43 mol, and CO production 12.68 mol. This study verified that aqueous urea could successfully replace the steam in autothermal reforming, which provides heat and increases syngas production, and reforming aqueous urea mixed with biodiesel has ultra-low sulfur, low carbon and little modifying the fuel system. Highlights: We analyze autothermal reforming of biodiesel mixing with aqueous urea. We determine best operating condition of ATR reforming for SOFC application. Mixing aqueous urea and biodiesel raises syngas production and reduces coke. Thermal neutral temperature reaches 700–800 °C for urea/biodiesel reforming. Highest syngas production occurs at UBR = 2 and OBR = 9 condition for 800 °C.